Effect of palm kernel cake and coconut-based formulated diet on Malaysia village chicken growth performances and meat quality - Mazlishah, Mohd Shahmi Hakimi; Zazali, Alias; Wan Syahidah, Hussain; Wan-Khadijah, Wan Embong; Abdullah, Ramli (Universiti Putra Malaysia, 2018)
The potential of the usage of palm kernel cake (PKC)-coconut based feeds has been considered as an alternative to commercial feed due to their low cost and abundance in availability and accessibility in Malaysia. However, previous studies have shown that the use of high fiber feed such as PKC resulted in poor performance of poultry due to low digestibility and palatability. In this study, a total of 400 village chickens from purebred and crossbred strains were reared to evaluate the effects of PKC and coconut-based feeding on their production performance. Body weight (BW), carcass evaluation, abdominal fat, meat conversion percentage, proximate analysis, and amino acid profile analyses were recorded in the study. The results showed that the Type A feed that contained higher fiber level resulted in poorer BW and carcass weight for both strains. It could be suggested that inconsistent size of fiber particles could influence the chicken’s digestibility. However, it was also shown that the quality of the meat of the village chicken and Type A feed were better in terms of having lower abdominal fat and crude fat contents. It also resulted in higher CP in crossbred strain meat which is correlated significantly with meat conversion percentage. Type B-fed chicken meat recorded low meat conversion percentage indicating higher formation in bone mass and feather, which is supported by the data of the ash in crossbred strain, indicating higher formation of mineral build-up such as bone mass. Furthermore, there were 11 amino acids that were recorded to be significantly higher in Type A-fed chicken meat compared with Type-B fed chicken meat, indicating a higher meat quality. In conclusion, the usage of Type-A feed as daily feed for village chicken was beneficial and exhibited prominent values in terms of quality and cost-effectiveness. However, more studies should be done to improve the digestibility and palatability of Type A feed to improve in their overall performances so that it can be used widely in poultry, particularly in village chicken farming.